2019
DOI: 10.1002/bin.1659
|View full text |Cite
|
Sign up to set email alerts
|

A review of behavioral interventions to enhance sports performance

Abstract: these studies use a multicomponent intervention, they often assess novel component combinations or apply an intervention to a scarcely studied or unstudied sport or target behavior.A recent poll found that three quarters of adults in the United States played sports when they were younger, and one quarter of adults continue to play sports throughout their lives, with more than 50 different sports included (Sports and Health in America, 2015). Additionally, participating in sports has numerous physical and socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 117 publications
1
65
0
1
Order By: Relevance
“…Behavior analytic procedures have been used to increase skill competency in over 20 sports (Schenk & Miltenberger, 2019). One specific behavior analytic technology that shows promise in sports applications is expert video modeling and video feedback, which has been implemented as either a stand-alone intervention or as part of a multicomponent intervention in many previous studies that address sports performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Behavior analytic procedures have been used to increase skill competency in over 20 sports (Schenk & Miltenberger, 2019). One specific behavior analytic technology that shows promise in sports applications is expert video modeling and video feedback, which has been implemented as either a stand-alone intervention or as part of a multicomponent intervention in many previous studies that address sports performance.…”
mentioning
confidence: 99%
“…Expert modeling consists of an individual who is fluent in a skill, deemed the "expert," exhibiting the skill accurately in the presence of a research participant. Video feedback consists of allowing a research participant to view his or her performance either just prior to or just after a skill attempt either with or without vocal feedback (Schenk & Miltenberger, 2019). Boyer et al (2009) investigated the impact of expert modeling and video feedback on gymnastic skills in competitive gymnasts.…”
mentioning
confidence: 99%
“…Applied behavior analysis has an expansive history of using behavioral techniques to enhance the training and performance of athletes in a long list of sports. The list includes football (Allison & Ayllon, 1980;Komaki & Barnett, 1977;Smith & Ward, 2006;Stokes, Luiselli, Reed, & Fleming, 2010;Tai & Miltenberger, 2017;Ward & Carnes, 2002), tennis (Allison & Ayllon, 1980;Ziegler, 1987), swimming (Hume & Crossman, 1992;Koop & Martin, 1983;Rogers, Hemmeter, & Wolery, 2010;Schonwetter, Miltenberger, & Oliver, 2014), soccer (Brobst & Ward, 2002;Ziegler, 1994), gymnastics (Allison & Ayllon, 1980;Boyer, Miltenberger, Batsche, & Fogel, 2009), track and field (Scott & Scott, 1997), basketball (Kladopoulos & McComas, 2001), in-line speed skating (Anderson & Kirkpatrick, 2002), martial arts (Harding, Wacker, Berg, Rick, & Lee, 2004), rugby (Mellalieu, Hanton, & O'Brien, 2006), and many more (Schenk & Miltenberger, 2019).…”
mentioning
confidence: 99%
“…Behavioral techniques have also enhanced skills using many procedures and intervention packages (Luiselli, Woods, & Reed, 2011;Schenk & Miltenberger, 2019). In a review by Schenk and Miltenberger (2019), they found that the enhancement of sports performance has been targeted using procedures such as consequence and antecedent manipulations, feedback procedures, skills training, and unique procedures such as habit reversal and acceptance and commitment therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation